Effect of Ethanol Extract of Jamblang Aceh (Syzygium cumini) in Diabetic Mice (Mus musculus) and Its Potential As Anti-Diabetic Agent - Ayu Nirmala Sari; Januardi Januardi; Diky Setya Diningrat (Elkawnie: Journal of Islamic Science and Technology, 2020)
Abstract : This study was designed to evaluate the anti-diabetic activity of the ethanol extract of Syzygium cumini leaves in alloxan-induced diabetes mice. The anti-diabetic activity of EDS was investigated in mice (Mus musculus SW.) Alloxan-induced diabetes. The effect of ethanol extract of Syzygium cumini leaves on normal blood glucose levels and oral glucose tolerance tests were studied in normoglycemic mice while the anti-diabetic effect was evaluated in alloxan-induced hyperglycemic mice. Ethanol extract of Syzygium cumini leaves (200 and 400 mg/kg) is given orally for 21 days. Glibenclamide (5 mg/kg, oral for 21 days) is used as a reference standard. Giving ethanol extract of Syzygium leaves causes a significant decrease in blood glucose levels in normoglycemic and hyperglycemic mice and also increases glucose tolerance test. Ethanol extract of Syzygium leaves reduces glycosylated hemoglobin levels, lactate dehydrogenase, and creatinine kinase in alloxan-treated mice. Ethanol extract of Syzygium leaves also improves TBARS oxidative stress parameters, catalase and superoxide dismutase activity and glutathione levels. The ethanol extract of Syzygium cumini leaves shows anti-diabetic activity through increased insulin secretion and this effect can be attributed to the content of flavonoids and phenolic compounds present in the ethanol extract of Syzygium cumini leaves.Abstrak : Penelitian ini dirancang untuk mengevaluasi aktivitas anti-diabetes dari ekstrak etanol daun Syzygium cumini (L) Skeels (EDS) pada mencit diabetes yang diinduksi aloksan. Aktivitas anti-diabetes EDS diselidiki pada mencit (Mus musculus SW.) diabetes yang diinduksi aloksan. Pengaruh ekstrak etanol daun Syzygium cumini (EDS) pada kadar glukosa darah normal dan uji toleransi glukosa oral dipelajari pada mencit normoglikemik sedangkan efek antidiabetik dievaluasi pada mencit hiperglikemik yang diinduksi aloksan. EDS (200 dan 400 mg/kg) diberikan secara oral selama 21 hari. Glibenclamide (5mg/kg, oral selama 21 hari) digunakan sebagai standar referensi. Pemberian EDS menyebabkan penurunan signifikan dalam kadar glukosa darah pada mencit normoglikemik dan hiperglikemik dan juga meningkatkan uji toleransi glukosa. EDS mengurangi kadar hemoglobin glikosilasi, laktat dehidrogenase, dan kreatinin kinase pada mencit yang diberi aloksan. EDS juga memperbaiki parameter stres oksidatif TBARS, aktivitas katalase dan superoksida dismutase dan kadar glutathione. Ekstrak etanol daun Syzygium cumini (EDS) menunjukkan aktivitas antidiabetik melalui peningkatan sekresi insulin dan efek ini dapat dikaitkan dengan kandungan flavonoid dan senyawa fenolik yang ada dalam ekstrak daun.